A O05 MUlti-center cohort Study of Oesophageal Injuries and related Clinical outcomes (MUSOIC) study. (7th December 2022) - Chidambaram, Swathikan; Kawka, Michael; Sultan, Javed; Phillips, Alexander; Scabbiolo, Zoe; Evan, Richard; Maynard, Nick; Vohra, Ravinder; Griffiths, Ewen; Gossage, James; Underwood, Tim; Walker, Robert; et al.
Abstract: Background: Perforation of the oesophagus (OP) represent a potentially lethal yet poorly managed clinical condition due to its rarity, variation in clinical presentation and little consensus on the optimal management of these patients. Previous studies have shown that timely and appropriate treatment of OPs is the most important determinant of patient outcomes, and a delay in initiating the correct management within 24 hours increased the mortality rate from 10% to over 60%. Historically, patients have been managed based on the personal experience and preference of the surgeon, and accordingly most patients underwent surgical management based on data from small retrospective case series. Depending on the cause of injury, location of perforation and status of the patient, options include conservative management; endoscopy (stenting or clipping); and surgery (drainage, diversion, primary repair, or oesophagectomy). Currently, there are no recent large-scale studies investigating the outcomes in oesophageal perforation, leading to a paucity of high-grade evidence on the management of oesophageal injuries. This study aims to characterise the variation in the management of OPs, update its epidemiology in the UK; and evaluate the mortality and morbidity outcomes of surgical and non-surgical modalities in managing OP. Methods: This was a multi-centred cohort study involving eligible centers from the Association of Upper Gastro-intestinal Surgeons for Great Britain and Ireland (AUGIS) research network. All adult patients who were admitted with a diagnosis of esophageal perforation (iatrogenic, spontaneous or traumatic causes) and managed as an inpatient for more than 24 hours were included in the study. Exclusion criteria were as follows: pediatric population; OP due to anastomotic leaks post-esophagectomy; and unavailability of data matching primary outcome measures. The time period for inclusion of patients was from January 2016 to December 2020. Investigators were asked to actively monitor patients and their electronic medical records to identify post-intervention complications up to 90 days from time of intervention if appropriate. The primary outcome was 90-day mortality. Other secondary outcomes included the incidence of complications secondary to OP or interventions; incidence of 30-day re-intervention; length of hospital stay (LOS) and intensive care unit (ICU) stay; readmission within 30 days; and recurrence. Results: During the study period 369 patients with oesophageal perforation from eight centres and were included in the study. The mean age of the population was 63 (18) years, body mass index was 25 (9)kg/m 2, 60% were male, 30% were ASA grade 3, and 41% ECOG performance status 0. The aetiology of OP was spontaneous in 57% and iatrogenic in 37%. The mean time from presentation to referral and intervention were 37 hours and 111 hours respectively. In patients transferred from a district general to a tertiary hospital the mean time from presentation to transfer was 100 hours. Surgery was used as the primary treatment approach in 31%, endoscopic intervention in 10% and conservative management in 56%. Thoractomy and laparotomy was used in 20% and 24% respectively, endosponge and endoscopic stent used in 11% and 7% respectively. 90-day mortality was 20% across the cohort, 30-day re-admission rate was 18%, mean ICU stay, and LOS were 10 days and 37 days respectively. 90-day mortality was significantly reduced in the surgery group (9%) when compared with endoscopic (24%) and conservative management groups (28%) (p<0.001). Multivariate analyses identified key patient, procedural, and treatment factors associated with mortality from oesophageal perforation. Conclusions: In a centralised oesophageal and gastric cancer service, the management of complex upper gastrointestinal conditions including oesophageal perforation is most commonly centralised to oesophageal and gastric cancer centres. This large multi-centre collaborative study provides robust data concerning modern practices of the management of oesophageal perforation in the UK. Through a detailed and highly granular dataset, we have examined factors associated with the patient pathway, presentation and treatment that are associated with mortality following oesophageal perforation.